Development and validation of an in-house handheld ELISA kit to detect glycosylated hemoglobin in human whole blood - Pyadala, Nagababu; Prudhvi Chand M; Ravi Kumar BN; Manno N Konyak; Ratna Giri Polvarapu (Asian Journal of Medical Sciences, 2022)
Background: Diabetes mellitus (DM) is known as one the oldest disease known to a human being and it is defined as a group of metabolic disorders characterized by the presence of hyperglycemia. Aims and Objectives: The present study describes the development and evaluation of a cost-effective and straightforward in-house handheld enzyme-linked immunosorbent assay (ELISA) kit for the determination of HbA1c in human whole blood of diabetic patients and is suitable for resource-poor settings. Materials and Methods: A total of 1056 specimens were collected for assay validation purposes. To check the proficiency of our diagnostic strategy, we compared our test results with high-performance liquid chromatography (HPLC) and a commercially available ELISA kit for HbA1c. The Institutional Ethical Committee approved this study (IEC). SPSS 16 statistical software analyzed all the data. The correlation regression was done to compare the assay. The level of significance of this study was P<0.001. Results: The sensitivity, specificity, and efficiency of the inhouse HbA1c ELISA kit range from 98.8%, 100%, and 99.24%. Conclusion: The newly developed in-house handheld HbA1c ELISA test kit is not only cost-effective, accurate, and straightforward but also gives good correlation with optimized methods such as HPLC and commercially available techniques in deciding the glycemic status of patients. Therefore, highly recommended for use in resource-poor settings in the management and diagnosis of DM.